The Acceptance of Cream Soups with the Addition of Edible Insects (Mealworm, T. molitor; House Cricket, A. domesticus; Buffalo Worm, A. diaperinus; Grasshopper, R. differens) among Young People and Seniors in Poland - Skotnicka, Magdalena; Mazurek, Aleksandra; Kowalski, Stanisław (Nutrients, 2023)
Research on the acceptance of consuming insects in one’s diet shows the increasing importance of this issue in the context of a sustainable food chain and ecology. Insects represent a promising food source due to their high nutritional value, efficiency in production, and minimal environmental impact, as well as the growing awareness of ecological issues. Despite these benefits, cultural and psychological barriers hinder the acceptance of consuming insects in Western countries. In this study, an assessment was made of the acceptance level of cream-type soups made from tomatoes and white vegetables with the addition of 20% flour from four insect species: mealworm (T. molitor); house cricket (A. domesticus); buffalo worm (A. diaperinus); and grasshopper (R. differens), compared to a control sample. One hundred and four subjects (55 seniors and 49 young adults) participated in this study. The acceptance level of various soups with insect flour was evaluated, considering different sensory parameters such as appearance, smell, taste, and texture. The research showed that older people have a lower acceptance for dishes containing insects compared to young adults, but the differences in the responses given were not statistically significant (p = 0.05), rejecting the assumption that insect-based products should be mainly targeted at young people. Of all the proposed test samples, the mealworm (T. molitor) was the most acceptable insect species in the tests in both taste versions for both age groups. The average score was 6.63 points on a 10-point scale. The products with the addition of grasshopper (R. differens) were rated the lowest. The acceptance level ranged between 4.23 and 4.38 points. A multiple regression analysis showed that taste and texture had the strongest influence on the overall acceptance of these dishes, and the results obtained were highly correlated with the general opinion of the testers. The increasing acceptance level and growing interest in this type of food can be a positive step towards sustainable and efficient food production.